BEHAVIOURAL FINANCE FOR EFFICIENT CORPORATE GOVERNANCE: TESTING THE EFFICIENT MARKET HYPOTHESIS AT THE BELGRADE STOCK EXCHANGE - Mijailovic, Olivera; Mizdraković, Vule M (The European Journal of Applied Economics, 2023)
The goal of this paper is to point out the limitations and reasons for the failure in modelling and concretization of scientific findings due to the assumption of rational behaviour of investors. Namely, behavioural corporate finance tends to add cognitive and psychological elements to the sophisticated mathematical and statistical models of modern corporate finance by observing and studying the behaviour of investors and managers. The theory does not offer a model for predicting the decision that will be made, but it provides the possibility to predict whether ‘riskier’ or ‘safer’ decision will be. The testing of the efficient market hypothesis, which represents the applied concept of a broader theory of the investors’ rational expectations, has been carried out in the empirical part of the research. The confirmed inefficiency on the capital market affects the investors in such a way that the decisions they make are not based on properly evaluated financial instruments. The results of the conducted empirical research disproved the hypothesis of traditional finance, which is based on the assumption of rational decision-making. Therefore, to understand the process of investment decision-making, it is necessary to use the approach offered by behavioural finance, since it introduces a component of irrationality.
Keywords: behavioural finance, psychology in economics, inefficiency, (ir)rational expectations, financial instruments